Do entrepreneurship challenges raise student’s entrepreneurial competencies and intention? - Silveyra-León, Geraldina; Rodríguez-Aceves, Lucía; Baños-Monroy, Verónica I. (Frontiers in Education, 2023)
Motivated by the question on what content and which pedagogical methodologies are effective in teaching entrepreneurship, this research tested whether entrepreneurial intention and entrepreneurial competencies changed after undergraduates attended an entrepreneurship challenge (ECH) experience. This pedagogical experience was carefully designed as a 5-week in-class education and a 1-week boot camp-type intensive activity. The research design was an empirical, survey-based pre- and post-study on a sample of 525 freshmen. Results showed an increase in entrepreneurial intention and in the entrepreneurial competencies measured (opportunity identification, evaluation and exploitation, and resources procurement). This research contributes to entrepreneurship education through the design and measurement of an effective program based on a previous framework for entrepreneurship courses and aligned with the education-through-entrepreneurship approach.